PENERAPAN SNP KABUPATEN/KOTA TAHUN 2017 PADA SARANA PRASARANA DINAS KEARSIPAN DAN PERPUSTAKAAN KUBU RAYA - Maulinda, Elin; Sahidi, Sahidi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study discusses then application of the 2017 Regency/Municipal SNP the Archives and Libraries Office of Kubu Raya. The method used is qualitative research, data collection techniques in the form of direct observation, documentation, and interviews. There are 4 informants who have special abilities in the field of libraries. The results showed that the location of the Archives and Library Office of Kubu Raya Regency was in a location that was not strategic and had no direction, and was behind the Education Office and Health Office so it was difficult to see. The area of the Kubu Raya Regency Library is not adequate because it is not in accordance with the National Library Standards. In the Regulation of the Head of the National Library of the Republic of Indonesia Number 8 of 2017 concerning National Standards for Regency/City Libraries for infrastructure, a minimum building area of 0.0082 per capita is calculated, which if calculated the library building area is 4,635 m2 per capita. Meanwhile, the building area of the Office of Archives and Library of Kubu Raya Regency is 8 x 24 m2 . Constraints experienced by the Kubu Raya Regency Library are library building and budget problems.Keywords: Facilities and Infrastructure, National Standards of Libraries, Public Libraries.